Type 2 Diabetes and Epigenetics: A Comprehensive Review - Roy , Abhijeet (Advancement and New Understanding in Medical Science Vol. 9, 2024)
Type 2 Diabetes is one of the major public health issues and a complex metabolic disorder strongly associated with genetic predisposition influenced by environmental factors and epigenetic regulation. Around 537 million people were diagnosed as diabetic in 2021 worldwide and it is predicted that the number will rise to 578 million by 2030, and 700 million by 2045. This review paper illustrated the role of epigenetics in the pathogenesis, progression, and detection of Type 2 Diabetes. A review study was performed for the articles published in English from 2000-2023 using Pub Med, and Google Scholar databases. Main underlining mechanisms of Type 2 Diabetes were identified: insulin resistance in the peripheral tissue and disintegrated insulin secretion. Epigenetics is “the study of changes in the gene functions that are mitotically and/or meiotically heritable and that do not entail a change in DNA sequence. Genome Wide Association Studies suggested that epigenetic regulation such as DNA methylation, Histone modification, microRNA strongly co-relates the development and progression of Type 2 Diabetes. Altered DNA methylation patterns in pancreatic islets, skeletal muscle, adipose tissue, from diabetic subjects compare to normal subjects was also found. Other risk factors like obesity, age, gender, impaired glucose tolerance, periconception and intrauterine environment may also have been linked with the possibilities of epigenetic changes. Lifestyle, socioeconomic condition, food habits are contributing to obesity and Type 2 Diabetes. Every year 2.8 million people die worldwide due to obesity and its complications. Epigenetics plays a crucial role by modifying the gene expression and establishing a relationship between the environment and genetic factors. Understanding the epigenetic mechanisms contributing to the development of Type 2 Diabetes is still limited.